A computational fluid dynamics analysis of oscillating bluefin tuna foil propulsion - Taray, Insha Ahmed (2021)
There is an on-going interest in analysing the flow characteristics of swimming fish-like bodies. Bio-inspired aquatic life has inspired some efficient and optimum designs for mankind. The design of both aerial and underwater vehicles has advanced over last few decades and new propulsion methods are being considered to further improve the existing designs. The study of fish locomotion has resulted in some very efficient motions and it has become an interest among scientists to formulate these motions. One such motion is thunniform locomotion (which means to swim like tuna) in which the undulations are confined to the tail (peduncle and caudal-fin) only. Bluefin tuna employs thunniform locomotion and has been associated with a high propulsive efficiency but with less experimental and computational base. Computational fluid dynamic analysis was done using Ansys Fluent for typical range of Strouhal numbers (0.183, 0.281 and 0.413) on a tuna-like body investigating the hydrodynamic forces and flow patterns of the tuna-swimming wake; the time-averaged resultant thrust for above three cases were found to be 0.728 N, 0.803 N and 0.9538. It is seen that higher the value of Strouhal number, more are the shed vortices in the wake. The thunniform motion designed in this study was compared with the existing 3D experimental studies through physical entity of thrust. The vortex shedding was recorded and visualized using curl of velocity and helicity method for vortex core region. The scope of this research has consequences in the design of aircrafts, airships, UAV’s, UUV’s, submarine-launched UAVs, winged vehicles to the jet-propelled take-off and submarines.